2022
DOI: 10.1002/celc.202200255
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Potential of Zero Charge Controls the Kinetics of Diazonium Salts Electropolymerization

Abstract: One of the central fundamental properties of solid/liquid interfaces is the potential of zero charge (pzc), where no excess charge prevails at the electrode surface. Applying potential on either side of the pzc can control adsorption of molecules on surfaces and is paramount for any interfacial process. However, the impact of pzc on electrode processes has been only demonstrated for reactions involving the adsorption of inorganic ions and gases. Here, the direct relationship between the pzc and electropolymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…A larger Q ads reveals higher accumulation efficiency towards NFZ, maybe due to the stronger interaction forces between NFZ and oxygen-containing groups, 38,39 as well as due to the different surface charges. 40,41 In conclusion, graphene oxidized at 1.4 V for 120 s (i.e. EGS-1.4) exhibits higher electron transfer ability and stronger adsorption ability toward NFZ oxidation.…”
Section: Enhanced Oxidation Of Nfz On Different Electrodesmentioning
confidence: 89%
“…A larger Q ads reveals higher accumulation efficiency towards NFZ, maybe due to the stronger interaction forces between NFZ and oxygen-containing groups, 38,39 as well as due to the different surface charges. 40,41 In conclusion, graphene oxidized at 1.4 V for 120 s (i.e. EGS-1.4) exhibits higher electron transfer ability and stronger adsorption ability toward NFZ oxidation.…”
Section: Enhanced Oxidation Of Nfz On Different Electrodesmentioning
confidence: 89%
“…In addition, another aspect is seldom accounted for by researchers working on FET sensing: the sensing surface will have a point of zero charge (PZC), where no excess charge is present at the electrode surface. A recent work by Darwish [ 47 ] has perfectly demonstrated that the kinetics of surface reactions depend on the surface PZC, and the adsorption and recognition of molecules on the surface can be controlled by applying potential, which will have a significant impact on the design and operation of the FET sensing interface. Furthermore, this may become a new issue for researchers to consider when functionalizing FET sensors in the future.…”
Section: Biosensor Designingmentioning
confidence: 99%
“…Adelaide, Andrew Abell, Jingxian Yu Linear peptides, constrained peptides and photoswitchable peptides ARC [ 199,200] Curtin, Nadim Darwish, Simone Ciampi Nanomaterials, including 2-D, electrosynthesis ARC [ 108,[201][202][203][204] Macquarie, Koushik Venkatesan Small molecules and conjugated polymer synthesis with redox and luminescence properties, biosensors, large area device fabrication, sensor and OLED device fabrication ARC [146][147][148][149] SNSF Melbourne, Colette Boskovic Switchable metal complexes, redox-active ligands ARC [ 121,[205][206][207][208][209] Melbourne, David Jones, Wallace Wong…”
Section: Referencesmentioning
confidence: 99%